Kemampuan Membedakan Bahasa Indonesia Baku dan Tidak Baku Oleh Siswa: Studi Kasus Siswa SMP Negeri 3 Mardingding - Darman Ginting (Institute of Computer Science (IOCS), 2020)
This research aims to describe the level of ability of students of State Junior High School 3 Mardingding in the ability to distinguish raw and non-standard Indonesian in Indonesian. The population of this study was 110 Mardingding State Junior High School students, and the study sample numbered 24 people who were taken randomly or randomly. This study uses descriptive methods. Data collection tool in the form of tests distinguishes the standard and not standard Indonesian as many as 70 questions. The data obtained is analyzed using percentage analysis techniques with the formula: The results of the analysis showed that the level of student mastery of the standard Indonesian of 61.65% and the student's mastery of non-standard language by 63.69%. While the average ability of students to distinguish raw and non-standard Indonesian is 70.04%.